Routledge handbook of law and society / edited by Mariana Valverde, Kamari Clarke, Eve Darian-Smith, and Prabha Kotiswaran. - Valverde, Mariana, 1955-; Clarke, Kamari Maxine, 1966-; Darian-Smith, Eve, 1963-; Kotiswaran, Prabha (Routledge handbooks., 2021)
This handbook provides a comprehensive, and truly global overview of the main approaches and themes within law and society scholarship or social-legal studies. A one-volume introduction to academic resources and ideas that are relevant for today's debates on issues from reproductive justice to climate justice, food security, water conflicts, artificial intelligence, and global financial transactions.